“Acedia” – an Old Demon in Modern Times - Kaminis, Ioannis (Forum Theologicum Sardicense, 2025)
Ioannis Kaminis, Acedia – an Old Demon in Modern Times. The goal of the current article is to present an overview of the so-called in patristic literature demon or passion of acedia and its activity as it is described in various monastic and patristic texts. Moreover, the article presents the signs of acedia-despondency, how it influences not only the monk but also every one of us and how this feeling-passion is still relevant in modern times, as one of the symptoms of depressive disorder. Apart from this the article presents some ways of overcoming this passion, ancient remedies taken from various patristic and monastic texts.